2018
DOI: 10.1111/jbi.13419
|View full text |Cite
|
Sign up to set email alerts
|

Environmental prevalence and the distribution of species richness across climatic niche space

Abstract: Aim The reciprocal relationship between geographical and ecological niche space known as Hutchinson's duality provides a powerful framework to analyse the relationship between biogeographical distributions and environmental variables. However, little attention has been given to how the structure of niche space is associated with the distribution of species across niche space itself. We examined whether environmental prevalence (i.e. the relative availability of different combinations of climatic conditions) ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 70 publications
(91 reference statements)
3
8
0
Order By: Relevance
“…species in the CFP that may face high levels of habitat decline due to both climate and land use change (>70% exposure) include California buckeye (Aesculus californica) and blue oak (Quercus douglasii), two tree species whose distributions are concentrated in the foothills of the Coast Ranges and the western Sierra Nevada regions that are predicted to face rapid climate change as well as exurban development during the next century (Figure1). Furthermore, while species with large range sizes tend to have broader environmental niches, homogenous environmental conditions may be prevalent across a region and therefore contain widespread species with narrow environmental affinities(Meyer & Pie, 2018), as we found for both blue oak and California buckeye. This finding highlights that broad spatial distributions may not buffer species from the consequences of global change, especially if their ranges are in highly vulnerable areas.Although niche breadth and range size were positively associated for our study species (r = .44; Supporting InformationFigure S4.1) and across taxa in previous research (Slatyer et al, 2013), they had F I G U R E 5 Proportion of variance in exposure to climate change (CC; a) and land use change (LUC; b) explained by rarity traits (range size, niche breadth, number of habitat patches and patch isolation), geographic traits (mean elevation, topographic heterogeneity and distance to coast), and representative concentration pathway (RCP) emissions scenario.…”
supporting
confidence: 55%
“…species in the CFP that may face high levels of habitat decline due to both climate and land use change (>70% exposure) include California buckeye (Aesculus californica) and blue oak (Quercus douglasii), two tree species whose distributions are concentrated in the foothills of the Coast Ranges and the western Sierra Nevada regions that are predicted to face rapid climate change as well as exurban development during the next century (Figure1). Furthermore, while species with large range sizes tend to have broader environmental niches, homogenous environmental conditions may be prevalent across a region and therefore contain widespread species with narrow environmental affinities(Meyer & Pie, 2018), as we found for both blue oak and California buckeye. This finding highlights that broad spatial distributions may not buffer species from the consequences of global change, especially if their ranges are in highly vulnerable areas.Although niche breadth and range size were positively associated for our study species (r = .44; Supporting InformationFigure S4.1) and across taxa in previous research (Slatyer et al, 2013), they had F I G U R E 5 Proportion of variance in exposure to climate change (CC; a) and land use change (LUC; b) explained by rarity traits (range size, niche breadth, number of habitat patches and patch isolation), geographic traits (mean elevation, topographic heterogeneity and distance to coast), and representative concentration pathway (RCP) emissions scenario.…”
supporting
confidence: 55%
“…The second class of explanation for the observed variation in climatic niche breadths has to do with the geographical availability of different climatic regimes, a phenomenon recently dubbed environmental prevalence (Meyer & Pie, 2018). The basic idea of environmental prevalence is the observation that climatic conditions are not isotropic, that is, not all environmental conditions are equally available.…”
Section: Discussionmentioning
confidence: 99%
“…Rather, given that some conditions are more prevalent, different lineages have adapted their environmental niches in proportion to their relative prevalence. Indeed, Meyer and Pie (2018) demonstrated that environmental prevalence was a better predictor of species richness in a variety of ecto-and endotherm taxa, explaining more of the geographical variation in species richness than the climatic variables themselves (e.g., annual mean temperature). In the context of climatic niches, several studies have recently F I G U R E 2 Variation in climatic niche breadth across terrestrial vertebrates (birds, amphibians, mammals, and squamates).…”
Section: Discussionmentioning
confidence: 99%
“…In this contribution, I analyze SARs at a biogeographic scale (extents of 10 6 to 10 7 km 2 and resolutions of grids of 10 2 to 10 3 km 2 ) using the amount of climatic space as the predictor (Meyer and Pie 2018). The approach is based on theoretical ideas related to Grinnellian niches (Jackson and Overpeck 2000;Soberón and Peterson 2005;Colwell and Rangel 2009;Peterson et al 2011).…”
Section: Introductionmentioning
confidence: 99%